News Value Analysis in Educational News on Kompas.com - Afniar Risma Nurhidayah; Wahyunengsih (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2023)
This study is entitled News Value Analysis in Educational News on Kompas.com. News value becomes a reference to determine whether a news story will be selected, prioritized, and reported by journalists. This research was conducted with the aim of knowing what news values are contained in educational news on Kompas.com, the dominant news values in educational news on Kompas.com, and the purpose of using news values in educational news. This research is a descriptive qualitative research. The data in this study are all words, phrases, and sentences contained in the Kompas website which is a type of educational news. The data source in this research is obtained by document study by analyzing the news value and entering the data into the analysis table. Based on the results of this study, it can be concluded that in Kompas.com educational news, 7 news values are obtained from 10 news values. The 7 news values, namely importance, actuality, impact, proximity, human interest, prominence and currentity have been applied well. News values that are news values are impact, proximity, and currentity. The use of news values in educational news is useful to increase the educational value of information.